An Analysis of Efficiency Patterns for a sample of Norwegian Bus Companies - Holvad, Torben (Proceedings from the Annual Transport Conference at Aalborg University, 2001)
In recent years significant progress has been made concerning measurement of efficiency in relation to productive activities, see e.g. Fried et al. (1993). In particular, non-parametric frontier methods such as Data Envelopment Analysis (put forward in Charnes et al. (1978)) and Free Disposal Hull (suggested by Deprins et al. (1984)) have been developed with applications across a wide range of sectors including transit services. This paper examines the efficiency variations of 157 of the 175 Norwegian subsidised bus companies using non-parametric frontier methods. A range of different efficiency measures within the non-parametric frontier tradition will be presented. The efficiency measures will be decomposed into pure technical inefficiency, scale inefficiency and inefficiency due to the convexity assumptions included in Data Envelopment Analysis (DEA). As such this information will provide a very detailed picture of the differences in performance among the included bus companies. Specific attention will be given to the efficient observations, in order to identify so-called superefficient observations. In addition, to the calculation of efficiency measures emphasis will also be put on possible explanations of the obtained results. This work will be undertaken within a regression analysis framework, whereby the efficiency scores are related to a set of independent variables. Explanations are important in order to determine the scope for enhancing efficiency for specific observations. The key issue will concern the extent to which efficiency variations are caused by controllable factors. In some cases measured inefficiency may be caused by factors outside the control of the individual company, e.g. the topographic or demographic conditions. The rest of the paper is structured as follows: Section 2 includes a brief overview of non-parametric efficiency measurement techniques emphasising the range of options available within this approach. In Section 3 the data used for the efficiency analysis are presented. The results of the efficiency analysis are presented in Section 4 including different types of efficiency measures and possible explanatory factors for the identified efficiency patterns. Section 5 concludes with final remarks including possible areas of further research.